Analysis of the interaction mechanism between straw soil rotary tillage blade during rotary tillage process - Zhaojie Wang; Xiangyu Li; Junwei Li; Yuntao Qiu; Tianlong Gu; Hailong Wang (Scientific Reports)
Abstract In response to the rotary ploughing equipment in the stubble land to implement protective operations, the stubble is large in number and strong in toughness, not easy to crush, resulting in rotary ploughing equipment to produce entanglement and increased resistance to rotary ploughing and other issues. In this study, researchers designed a bionic rotary tillage blade (B-RTB) based on the bionic structural equations of the Marmota claw. A straw-soil complex shear performance test was conducted to investigate the effect of straw on soil shear strength. Based on EDEM software, we constructed a soil-rotary tillage cutter-straw interaction model, carried out straw-soil-rotary tillage cutter interaction mechanism analysis. Conducted a three-factor, three-level quadratic regression orthogonal test with the bionic rotary tillage blade (B-RTB) bending angle, tine spacing, and cutter roller rotational speed as the test factors, and with the rotary tillage torque and the number of straw contact bond breaks as the response indexes to determine the optimal parameter combinations of the rotary tillage torque and the number of straw contact bond breaks. Soil bin tests were conducted to verify the anti-entanglement and drag reduction performance of the bionic rotary tillage blade (B-RTB). The straw-soil composite shear performance test showed that: under the same positive pressure, when the straw content increased from 0 to 0.5%, the shear strength of the straw-containing soil composite was proportional to the vertical pressure. The results of the orthogonal test showed that under the conditions of rotary ploughing operation with straw spreading, the bending angle of 122°, the tine spacing of 14.5 mm, and the cutter roll speed of 255 r·min− 1 were the better parameter combinations, at which time the minimum rotary torque of 15.327 N·m was achieved, and the maximum number of straw contact bond breaks was 2443. In the soil bin test, compared with the conventional rotary tillage blade (C-RTB), the rotary torque of the bionic rotary tillage blade (B-RTB) was reduced by 6.50%. When no straw was laid, and the rotary torque of the bionic rotary tillage blade (B-RTB) was reduced by 9.45% and the straw breakage rate was increased by 6.67% when straw was laid, which effectively realized the requirements of the rotary tillage anti-entanglement and obstruction reduction technology. The results of this study can provide a reference for the visualization of touchdown components and the analysis of rotary tillage interaction mechanisms in mixed material operating systems.